The impacts of organizational culture, knowledge management and employee engagement on job satisfaction: The case of supportive service officers in Mongolia - Tsogtsuren Bayasgalan; Ravdansuren Chantsaldulam (Apstract: Applied Studies in Agribusiness and Commerce, 2017)
Employee’s job satisfaction is one of the main influential factors for the effectiveness of human resource development. The aim of this study is to investigate the impacts of organizational culture, knowledge management and employee engagement on job satisfaction among public officers. This research topic has been studied and is well-known in worldwide. In Mongolia, context the topic of study has been developed at low level. Data collected from the public-sector employees that understand to impact of job satisfaction. In the research, 213 participants participated who work in public organizations of Mongolian cities such as Ulaanbaatar, Darkhan and Erdenet and districts near to Ulaanbaatar city, including Nalaikh, Khutul, Baganuur. Therefore, the research methodology organized and used some information from statistical calculations in Mongolia. The results showed that impact of all factors such as organizational culture, knowledge management and employee engagement had a positive relationship on job satisfaction. It means that public servants can take care of organizational culture, knowledge management and employee engagement to remain and make their employees happy, as the more satisfied employees are, the more productive they are than those who are less satisfied. This study discussed the effects of above mentioned results, the implications for theory and practice along with the limitations of the research and the implications for further research. Data were used SPSS and SmartPLS 3.0 to test the relationships between variables.